Slaughterhouses fungal burden assessment - Viegas, Carla (2018)
In slaughterhouses, the biological risk is present not only from the direct or indirect contact with animal matter, but also from the exposure to bioaerosols. Fungal contamination was already reported from the floors and walls of slaughterhouses. This study intends to assess fungal contamination by cultural and molecular methods in poultry, swine/bovine and large animal slaughterhouses. Air samples were collected through an impaction method, while surface samples were collected by the swabbing method and subjected to further macro- and micro-scopic observations. In addition, we collected air samples using the impinger method in order to perform real-time quantitative PCR (qPCR) amplification of genes from specific fungal species, namely A. flavus, A. fumigatus and A. ochraceus complexes. Poultry and swine/bovine slaughterhouses presented each two sampling sites that surpass the guideline of 150 CFU/m3. Scopulariopsis candida was the most frequently isolated (59.5%) in poultry slaughterhouse air; Cladosporium sp. (45.7%) in the swine/bovine slaughterhouse; and Penicillium sp. (80.8%) in the large animal slaughterhouse. Molecular tools successfully amplified DNA from the A. fumigatus complex in six sampling sites where the presence of this fungal species was not identified by conventional methods. This study besides suggesting the indicators that are representative of harmful fungal contamination, also indicates a strategy as a protocol to ensure a proper characterization of fungal occupational exposure.